Encapsulation by Directed PISA: RAFT‐Based Polymer‐Vesiculated Pigment for Opacity Enhancement in Paint Films. Issue 10 (13th April 2021) - Nguyen, Duc; Huynh, Vien; Lam, Minh; Serelis, Algirdas; Davey, Tim; Paravagna, Olga; Such, Chris; Hawkett, Brian
Abstract: A novel method is demonstrated to encapsulate titanium dioxide pigment using directed polymerization‐induced self‐assembly (PISA) with reversible addition‐fragmentation chain‐transfer (RAFT) controlled emulsion polymerization. The polymerization is carried out in a batch process in which both styrene (Sty) and the pigment are emulsified using triblock amphiphilic macro‐RAFT copolymers as stabilizers. RAFT‐controlled chain growth leads to directed lamellar self‐assembly, forming polystyrene (PS) shells' encapsulating pigment particles with 100% efficiency. The pigment resides either at centers of single‐void vesicles or within the interior of multivoid vesiculated particles. The presence of complex morphologies such as spherical particles, nanofibers, nanoplatelets, and polymer vesicles confirms the PISA pathway. The process is optimized to preferably produce polymer‐vesiculated pigment for use as an enhanced opacifier in water‐based paint. Abstract : This is the first report of polymer‐vesiculated pigment synthesis in which titanium dioxide (TiO2 ) particles are encapsulated within the interior of polymer vesicles using the newly described directed polymerization‐induced self‐assembly (PISA) process. Such particles act as very efficient light scatters (opacifiers) in paint films, resulting almost 50% reduction in pigment use.